(untitled) (Hematology Meeting Reports, 2009)
The coagulation protease cascade and the fibrinolytic system are leading to the synthesis of two serine-proteases that are essential for normal hemostasis but these enzymes also play important regulatory roles in angiogenesis, cancer cell migration and tumor growth. Tissue factor (TF) is the physiological trigger of coagulation cascade and is mainly regulated by TFPI-1 (tissue factor pathway inhibitor), a kunitz-domain serine protease inhibitor. But, another protein analogous to TFPI-1 and named TFPI-2 is also present in large amounts in extracellular matrices (ECM), and has been identified as playing an important role in cancer invasion.